2009
DOI: 10.1007/s00330-009-1565-5
|View full text |Cite
|
Sign up to set email alerts
|

Workplace experience of radiographers: impact of structural and interpersonal interventions

Abstract: Purpose: Within the framework of organisational development, an assessment of the workplace experience of radiographers (RGs) was conducted. The aims of this study were to develop structural and interpersonal interventions and to prove their effectiveness and feasibility.Methods: A questionnaire consisting of work-related factors, e.g. time management and communication, and two validated instruments (Workplace Analysis Questionnaire, Effort-Reward Imbalance Scale) was distributed to all RGs (n = 33) at baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This study's conclusion that power hierarchy within healthcare interactions is a factor in the display of DBs chimes with literature. Workers within hospitals often perceive that powerful, revenue-generating doctors are tolerated for DB due to the apparent consequences of confronting them (14,22,23). A study conducted by The American College of Physician Executives on doctors' behaviour found that 38.9 percent of the participants agreed that "physicians in my organization who generate high amounts of revenue are treated more leniently when it comes to behaviour problems than those who bring in less revenue (24).…”
Section: Discussionmentioning
confidence: 99%
“…This study's conclusion that power hierarchy within healthcare interactions is a factor in the display of DBs chimes with literature. Workers within hospitals often perceive that powerful, revenue-generating doctors are tolerated for DB due to the apparent consequences of confronting them (14,22,23). A study conducted by The American College of Physician Executives on doctors' behaviour found that 38.9 percent of the participants agreed that "physicians in my organization who generate high amounts of revenue are treated more leniently when it comes to behaviour problems than those who bring in less revenue (24).…”
Section: Discussionmentioning
confidence: 99%